(untitled) (International Congress on Economics, Management and Business Studies, 2026)
This article describes the reforms implemented by Amir Amanullah Khan in the field of press and the impact of newspapers and magazines created at that time on social life. The article is also enriched with the scientific works of scholars studying the history of Afghanistan. The article cites famous historical newspapers in Afghanistan as examples and substantiates them with scientific literature.